The Power of Supply Chain Visualisation: Developing a framework for visualising the supply chain - Ahmed, Wafaa Ahmed Hamed (2017)
There is extensive research in the area of supply chain visibility and its importance for supply chain management, integration and collaboration. However, there is a real lack of research emphasising Supply Chain Visualisation (SCV). SCV constitutes an important part under the umbrella of supply chain visibility that specifically deals with the process of visualising the supply chain, including determining the relevant supply chain information to visualise and developing the appropriate supply chain visuals in order to generate insights that lead to better supply chain understanding. Despite the importance of SCV, there is a lack of well-established process for visualising the supply chain and very little consideration has been made to the developments in fields such as Geographical Information Systems (GIS) and other visualisation technologies, and their role in improving SCV. Therefore, this research aimed to develop a framework that provides a structured approach for SCV considering the main managerial and technological factors that can affect the visualisation process. To develop the framework, the current software capabilities including GIS for visualisation had been examined and a case study for visualising the changes in the global value chain of the apparel industry had been conducted to investigate the importance and capabilities of SCV. Undertaking this process had revealed valuable insights that were incorporated to the development of the framework. Thereafter, the framework had been experimented in the automotive sector to showcase its applicability in different contexts. This dissertation represents a starting point that calls for further research emphasising supply chain visualisation with the current software capabilities for better supply chain understanding, and effective supply chain management.